The Influence of Training, Work Motivation, and Discipline on Employee Performance (Literature Review) - Rala Satumalay, Taufan; Khaerudin (Dinasti International Journal of Digital Business Management, 2025)
This study aims to examine the effects of training, work motivation, and discipline on employee performance. The research employs a literature review method, which involves collecting and analyzing previous studies to draw more comprehensive conclusions. Data sources include national and international journals obtained through Google Scholar. The results of the literature review indicate that training, work motivation, and discipline have a significant relationship with employee performance. In the training variable, five research journals revealed that training has a positive impact on improving employees' skills and productivity. For the work motivation variable, one journal found that work motivation does not significantly affect employee performance, while four other journals stated that high motivation can enhance employee performance through increased enthusiasm and dedication to work. In the work discipline variable, all five journals agreed that work discipline contributes to creating order, responsibility, and compliance with company regulations, thus positively impacting employee performance.